Corrigendum: Quercetin Induces Apoptosis Via Downregulation of VEGF/Akt Signaling Pathway in Acute Myeloid Leukemia Cells (Frontiers in Pharmacology, (2020), 11, 10.3389/fphar.2020.534171) - Shi, Huan (Frontiers Media S.A., 2022)
10.3389/fphar.2020.640750